2021
DOI: 10.2147/copd.s274846
|View full text |Cite
|
Sign up to set email alerts
|

Consistent Pulmonary Drug Delivery with Whole Lung Deposition Using the Aerosphere Inhaler: A Review of the Evidence

Abstract: Metered dose inhalers (MDIs) are one of the most common device types for delivering inhaled therapies. However, there are several technical challenges in development and drug delivery of these medications. In particular, suspension-based MDIs are susceptible to suspension heterogeneity, in vitro drug-drug interactions, and patient handling errors, which may all affect drug delivery. To overcome these challenges, new formulation approaches are required. The Aerosphere TM inhaler, formulated using cosuspension d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 58 publications
2
7
0
1
Order By: Relevance
“…Клинический интерес вызвали исследования с использованием гамма-сцинтиграфии и функциональной визуализации органов дыхания. Установлено, что лекарственное соединение ГП/ФФ эффективно откладывается в центральных и периферических дыхательных путях, обеспечивая значимое увеличение ряда показателей внешнего дыхания [32][33][34].…”
Section: рациональная фармакотерапияunclassified
“…Клинический интерес вызвали исследования с использованием гамма-сцинтиграфии и функциональной визуализации органов дыхания. Установлено, что лекарственное соединение ГП/ФФ эффективно откладывается в центральных и периферических дыхательных путях, обеспечивая значимое увеличение ряда показателей внешнего дыхания [32][33][34].…”
Section: рациональная фармакотерапияunclassified
“…Furthermore, the technology is characterized by higher consistency of dose (within a 15% range), irrespective of any shaking-firing delay up to one minute 55,56 . Altogether, these improvements lead to a more efficient lung deposition of the pharmacological compound, compared to both non extra-fine DPIs 57 and suspension pMDIs 58 . Concerning breath-actuated pMDIs, a flow triggered mechanism is incorporated into the device and a spring releases the dose upon activation of that mechanism 59 .…”
Section: Interactive Relationships Between Patients and Inhalation Devicesmentioning
confidence: 99%
“…• Missing comparators of potential interest: While ICS inhalers are not indicated by Health Canada for use in patients with COPD, and current COPD guidelines 5,6 do not endorse their use, the clinical expert consulted by CADTH indicated that with the current availability of LABA-LAMA inhalers, patients needing triple therapy who are not adequately controlled on a LABA-LAMA inhaler may be escalated to a LABA-LAMA plus ICS combination. The clinical expert further indicated that the use of an independent ICS inhaler allows for more individualization of ICS dose than the use of an ICS-LABA plus LAMA combination; thus, a separate ICS inhaler may be preferred by some clinicians or patients.…”
Section: Cadth Appraisal Of the Sponsor's Economic Informationmentioning
confidence: 99%
“…5 Aerosphere offers advantages over traditional MDIs, such as consistent delivery of drugs across patient conditions, optimal particle size, and effective delivery of the particles to peripheral and central airways. 6 The components of Breztri Aerosphere are available in other formulations that also have Health Canada-approved indications for the management of COPD. 3,4 The objective of this review was to perform a systematic review of the beneficial and harmful effects of budesonide plus glycopyrronium plus formoterol fumarate (BGF) dihydrate inhalation aerosol (Breztri Aerosphere 182 mcg, 8.2 mcg, 5.8 mcg per metered actuation) for long-term maintenance treatment of patients with COPD, to reduce exacerbations of COPD, and to relieve symptoms, including chronic bronchitis and/or emphysema.…”
Section: Introductionmentioning
confidence: 99%